IMPLEMENTASI KEBIJAKAN LAYANAN CO WORKING SPACE RAMAH DIFABEL SEBAGAI KONSEP PENGEMBANGAN JOGJA SMART PROVINCE: ( Studi Kasus di Dinas Komunikasi dan Informatika DIY ) - Ambarwati, Dina Bayu; Syakdiah, Syakdiah; Kusumawiranti , Retno (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
The Disabled Friendly Diskominfo Co Working Space (DCS) service at Diskominfo Yogyakarta was inaugurated on Friday, August 24, 2018, to facilitate the star-ups and digital creators. Based on this, researchers are interested in studying the Implementation of Disability Friendly Co Working Space Service Policy as a Jogja Smart Province Development Concept in Yogyakarta Diskominfo. The aim is to find out the implementation of Co Working Space services for people with disabilities as a concept for developing Jogja Smart Province and the factors that influence services. This research uses descriptive qualitative research methods with data collection techniques: observation, interviews, and documentation, and data analysis techniques: data reduction, data presentation and conclusions. The results of the implementation of the implementation policy of the Working Space service for the disabled-friendly Working Room as the concept of developing Jogja Smart Province were seen from several indicators with the achievement of a target of 100% for workshop activities as many as six times a year and 75% of service use, in the guestbook in 2019 as many as 476 visitors use of space for community events there are 280 people, there are 140 workshop activities